Protocol for a QUALICOPC study in a Malaysian setting: Primary care pharmacy services system performance and T2DM older adults' quality of life evaluation. - Nurain Suleiman; Ishtiaq Ahmad; Motoyuki Yuasa (PLoS ONE)
Pharmacists may play a crucial role in enhancing the primary care (PC) system by offering convenient patient care and leveraging their expertise to promote community health through pharmaceutical care and value-added services. Given the significant healthcare issue of Type 2 Diabetes Mellitus (T2DM) in Malaysia and other Asian countries, the associated treatment costs have become a global economic concern. The increasing prevalence of T2DM in Malaysia, particularly among older adults, is intensifying its clinical and economic impact on the country. To address this, the current study aims to evaluate the effectiveness of PC pharmacies using the Quality and Costs of Primary Care (QUALICOPC) Survey, which is widely used in Europe and other developed and developing countries. This research seeks to collect experience and value feedback from older adults with T2DM or their caregivers, and job satisfaction feedback from pharmacy staff. Additionally, the quality of life (QOL) of older adults with T2DM will be assessed among the patients who are respondents in this study. This study will use the adapted and validated QUALICOPC questionnaires that are in line with international standards and tailored to the Malaysian context. An expert panel, including the Pharmaceutical Services Division of the Ministry of Health (MOH) Malaysia and the Kulliyyah of Pharmacy at the International Islamic University Malaysia (IIUM), has been involved in the content validity of the adapted QUALICOPC questionnaires. The QUALICOPC questionnaires will be validated for the construct with a minimum of 38 samples for each client experience questionnaire, 30 samples for each value questionnaire, and 19 samples for the staff questionnaire. The survey will involve 192 samples from each group of T2DM older adults or caregivers and all corresponding public PC pharmacy staff. The QOL will be evaluated using the EuroQol (EQ) 5-dimensions 5-levels [EQ-5D-5L] and an EQ visual analog scale (EQ-VAS). The findings from this study will be valuable for informing the World Health Organization (WHO) and the Malaysian government in designing more effective health policies.